ENABLING INTELLIGENT AGENTS AND THE SEMANTIC WEB FOR E-COMMERCE - Kats, Yefim H. (International Journal of Computing, 2014)
This paper examines an impact of the growing intelligent agent technologies and the Semantic Web on the phenomenon of e-commerce. We discuss the problems – technical as well as legal – arising from the emergence of the new forms of intelligent software and consider the possible solutions. In particular, we review how the integration of the Semantic Web and intelligent agents can provide a new environment for the secure and scalable e-commerce applications.